1980
DOI: 10.1007/bf01320626
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated free fatty acids inactivate animal enveloped viruses

Abstract: Unsaturated free fatty acids such as oleic, arachidonic or linoleic at concentrations of 5-25 microgram/ml inactivate enveloped viruses such as herpes, influenza, Sendai, Sindbis within minutes of contact. At these concentrations the fatty acids are inocuous to animal host cells in vitro. Naked viruses, such as polio, SV40 or EMC are not affected by these acids. Saturated stearic acid does not inactivate any viruses at concentrations tested. Though the mode of action of unsaturated fatty acids is not understoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
0
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 18 publications
5
69
0
1
Order By: Relevance
“…Fatty acids and fatty acid-containing molecules were found to inactivate enveloped viruses, HSV-1 included, by disintegrating the virus lipid envelope (Horowitz et al, 1988;Kohn et al, 1980;Thormar et al, 1987). On the other hand, Hilmarsson et al (2005) observed that the acidic environment makes HSV more sensitive to certain virucidal lipids (fatty alcohols and lipids), possibly by ionic changes in the envelope proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids and fatty acid-containing molecules were found to inactivate enveloped viruses, HSV-1 included, by disintegrating the virus lipid envelope (Horowitz et al, 1988;Kohn et al, 1980;Thormar et al, 1987). On the other hand, Hilmarsson et al (2005) observed that the acidic environment makes HSV more sensitive to certain virucidal lipids (fatty alcohols and lipids), possibly by ionic changes in the envelope proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids are well-known antimicrobial substances with activity in vitro against gram-positive and gram-negative bacteria (22)(23)(24)(25)(26), fungi (27,28), and enveloped viruses, including influenza (29)(30)(31) (34,35) showed that staphylococci, streptococci, and candida rapidly decreased in number after being deposited on normal skin, whereas acetone-washed skin allowed greater persistence of the microorganisms. When skin surface acetone extracts were replaced on washed skin, the increased bacterial counts were not seen.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrolyzed linseed oil, which contains 52% ALA and pure ALA were found to be capable of killing methicillinresistant Staphylococcus aureus [21]. Both LA and AA were reported to inactivate animal herpes, influenza, Sendai, and Sindbis virus within minutes of contact [22]. LA administered orally as safflower oil (which contains 76% LA) produced remission of mycosis fungoides, a rare skin disease of viral etiology, in dogs that correlated with an increase in the plasma levels of LA and AA [23].…”
Section: Pufas Have Anti-bacterial Anti-viral Anti-fungal and Antimentioning
confidence: 97%
“…In the light of these facts, it will be interesting to study whether a sub-clinical deficiency of LCPUFAs, decreased formation of LXs and resolvins occurs in subjects who develop various types of infections and their complications such as sepsis. Since, LCPUFAs can inactivate enveloped viruses including influenza [22,33], it is probably worthwhile to study the effect of various fatty acids on bird flu virus and if so, whether increased intake of these fatty acids could reduce the risk of flu.…”
Section: Pufas Have Anti-bacterial Anti-viral Anti-fungal and Antimentioning
confidence: 99%